Alfabetização e letramento: concepções presentes no ensino da linguagem escrita - Bordignon, Lorita Helena Campanholo (2016)
In the history of Brazilian education, the concepts and teaching practices related to literacy have undergone several changes. It is believed that this fact is due of the different economic, social, cultural and political issues that have permeated as a backdrop the schooling process in Brazil. Therefore, it is important to know and understand the history of literacy in Brazil by identifying what it is still present in current pedagogical practices. The objective this study was to know the writing concepts and teaching of written language that are present in students’ notebooks of class of 1st year literacy cycle of six urban public schools of the municipalities of the 32nd Education Management of Santa Catarina state. This is a qualitative research, with documentary character, from the analysis of 31 students’ notebooks of the years of 2012, 2013 and 2014. The notebooks were of students from six urban schools with classes of 1 year literacy cycle of the municipal school system of the six municipalities of the 32nd Secretary of Regional Development, Quilombo, Santa Catarina state. Students’ notebooks were submitted to qualitative analysis from of the content analysis method proposed by Bardin (2011). It was possible revealed that remain in classrooms some decontextualized activities, still based on traditional methods of teaching, with activities based on cartilhescos models such as repeat activities and copy of syllables and words. However, in other extracts it was revealed that the pedagogical concepts utilized by educators have been modified, searching to meet the current educational needs, and point to literacy perspective, designing writing and the teaching of writing as a interaction instrument between the subjects inserted in social and cultural contexts. Thus, from the reflections made in the research’ results, is expected to contribute with possible teacher formation policies and especially with literacy work.